Mini Review: Organization Commitment, Organization Sustainability, Resilience, Community Social Behavior, Transformational Leadership - Agustian Zen (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of study is to present the findings of variables of organizational commitment, individual or employee resilience, social behavior of society, transformational leadership and organizational sustainability. Method used is qualitative with a review of the literature review. The results of the literature review from the perspective and findings of the review article relate to variables with positive and significant results such as resilience variables with organizational commitment, customer behavior variables not found directly with organizational commitment variables, organizational sustainability with organizational commitment there are articles that state positively and significantly from exposure to review articles in above. Furthermore, resilience and transformational leadership there are several articles found by researchers that state positive and significant. It's just that from this article there are no research results where the five independent variables above with dependent variables have been studied and there are results. Also, dependent variables with intervening variables of existing research results that state positive and significant.